2012
DOI: 10.1371/journal.pone.0043399
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α Regulates Chemotactic Migration of Pancreatic Ductal Adenocarcinoma Cells through Directly Transactivating the CX3CR1 Gene

Abstract: CX3CR1 is an important chemokine receptor and regulates the chemotactic migration of pancreatic ductal adenocarcinoma (PDAC) cells. Up to now, its regulatory mechanism remains largely undefined. Here, we report that hypoxia upregulates the expression of CX3CR1 in pancreatic cancer cells. When hypoxia-inducible factor (HIF)-1α expression was knocked down in vitro and in vivo, the expression of CX3CR1 was significantly decreased. Chromatin immunoprecipitation assay demonstrated that HIF-1α bound to the hypoxia-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 23 publications
3
54
1
Order By: Relevance
“…The mechanism responsible for receptor upregulation in tumors is unclear. CX 3 CR1 is not modulated in vitro by several cytokines (21), but recent studies suggested a role for hypoxia and NF-kB in receptor regulation in pancreatic cancer (47,48), a finding that we did not confirm (21) (and data not shown).…”
Section: Discussioncontrasting
confidence: 92%
“…The mechanism responsible for receptor upregulation in tumors is unclear. CX 3 CR1 is not modulated in vitro by several cytokines (21), but recent studies suggested a role for hypoxia and NF-kB in receptor regulation in pancreatic cancer (47,48), a finding that we did not confirm (21) (and data not shown).…”
Section: Discussioncontrasting
confidence: 92%
“…siRNA against protein kinase C (PKC) was purchased from Santa Cruz Biotechnology (sc-29449). siRNAs against HIF-1a and pcDNA-HIF-1a plasmids were prepared as previously described (4,16). The fulllength fascin cDNA (GenBank no.6624) was ligated into expression vector pEGFP-C1 (Invitrogen) and verified by sequencing.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Hypoxia-inducible factor-1 (HIF-1; consists of highly regulated HIF-1a and a constitutively expressed HIF-1b) is the most important transcription factor as a result of intratumoral hypoxia, which can mediate many adaptive physiologic responses (3). In pancreatic cancer, HIF1a expression levels are associated with tumor progression, fibrotic focus, angiogenesis cell migration, and hepatic metastasis (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…A developing body of evidences has shown that hypoxia inducible factor-1α (HIF-1α) is involved in crucial aspects of cancer biology, including angiogenesis, proliferation, energy metabolism and invasion (Hiraki et al, 2012;Schito et al, 2012;Zhao et al, 2012;Cheng et al, 2013). Although the relevance of HIF-1α on the prognosis in NSCLC has been investigated, conflicting results have been reported from different laboratories (Volm et al, 2000;Hirami et al, 2004;Swinson et al, Wei Ping, Wen-Yang Jiang, Wen-Shu Chen, Wei Sun, Xiang-Ning Fu* Hung et al, 2009;Park et al, 2011).…”
Section: Introductionmentioning
confidence: 99%